APLIKASI PEMBELAJARAN BAHASA INGGRIS MENGGUNAKAN INSTANT MESSENGER (Information Technology and Telematics, 2014)
abstraction : To test the English language skills, especially for those whose mother tongue other than English, one of them by using the TOEFL. Implementation of these tests most still use paper media (paper-based) to present the matter as well as to write the answers. To calculate and evaluate the test results require more time and more accuracy. This happens because during this test was performed using a booklet and answer sheet. Documenting the use of paper allows for many mistakes and also requires a lot of storage place for documentation of.This study will make English language learning applications menggungakan Instant Messenger. The goal is to facilitate the Siwa get exercises. Instant Messenger is a form of short message communication between two or more people using typed text. This system will be used by students to access English language learning data by typing a query as input (input), and then the system will display the specific language learning data query is entered as the output (the output).English language learning application using Instant Messenger was created using the Java programming language with the help of Netbeans IDE 7.0. As for the database used is MySQL.This study resulted in an application that allows students to access the learning data with a database of English documents in the form of Java.Keywords: Learning English, Instant Messenger, Java, MySQL.